The Biological and Biophysical Properties of the Spider Peptide Gomesin - Tanner, J.; Deplazes, Evelyne; Mancera, Ricardo (M D P I AG, 2018)
This review summarises the current knowledge of Gomesin (Gm), an 18-residue long, cationic anti-microbial peptide originally isolated from the haemocytes of the Brazilian tarantula Acanthoscurria gomesiana. The peptide shows potent cytotoxic activity against clinically relevant microbes including Gram-positive and Gram-negative bacteria, fungi, and parasites. In addition, Gm shows in-vitro and in-vivo anti-cancer activities against several human and murine cancers. The peptide exerts its cytotoxic activity by permeabilising cell membranes, but the underlying molecular mechanism of action is still unclear. Due to its potential as a therapeutic agent, the structure and membrane-binding properties, as well as the leakage and cytotoxic activities of Gm have been studied using a range of techniques. This review provides a summary of these studies, with a particular focus on biophysical characterisation studies of peptide variants that have attempted to establish a structure-activity relationship. Future studies are still needed to rationalise the binding affinity and cell-type-specific selectivity of Gm and its variants, while more pre-clinical studies are required to develop Gm into a therapeutically useful peptide.